Atlas anatomi Lippincott Williams & Wilkins / Patrick W. Tank, Thomas R. Gest ; alih bahasa, Huriawati Hartanto ; editor, Rina Astikawati. - TANK, Patrick W.; Gest, Thomas R.; Huriawati Hartanto; Rina Astikawati (Erlangga, 2010)
xv, 432 hlm. : ilus. ; 28 cm (3 eks.)